P054 Effects of treatment of sleep disordered breathing on actigraphic sleep measures and daytime functioning in children with Down syndrome. (9th November 2022) - Horne, R; Shetty, M; Davey, M; Walter, L; Nixon, G
Abstract: Background: Children with Down syndrome (DS) are at increased risk of obstructive sleep disordered breathing (SDB), which is associated with sleep disruption affecting daytime functioning. We examined the effects of treatment of SDB on sleep and daytime functioning in children with DS. Methods: Children with DS and SDB (n=34) completed a baseline and follow-up study which included 7 days of actigraphy in conjunction with a parental sleep diary. Parents also completed a number of questionnaires assessing sleep, behaviour, daytime functioning and quality of life (QOL). All children had overnight polysomnography (PSG) at baseline and 24 had PSG at follow-up. Results: 15 children (44%) were treated. At baseline the treated group had more severe SDB at baseline compared to the untreated group: obstructive apnoea hypopnoea index (OAHI) 29.3 ± 38.2 events/h vs 3.3 ± 5.2 events/h (p<0.01). Actigraphy showed no significant differences in total sleep time or sleep efficiency from baseline to follow up in either the treated or untreated group. Wake after sleep onset increased at follow-up in the untreated group (p<0.01). The sleep disturbance (p<0.01) and total problems (p<0.05) scales on the OSA-18 and the SDB subscale on the Pediatric Sleep Problem Survey Instrument (p<0.01) improved in the treated children. No changes were seen in any of the measures in the untreated children. Conclusions: Treatment of SDB improves QOL, despite treatment having no demonstrable impacts on actigraphic sleep measures. In contrast despite having less severe SDB children who were untreated had no improvements in QOL and increased sleep disruption.